Perbandingan Kadar Fe dan Zn pada Penderita TB dengan Riwayat DM dan Non DM - Latifah, Aminahtun; Kurniasih, Dewi; Wahyuni, Evi (Journal of Telenursing (JOTING), 2024)
This study aims to determine the levels of Fe and Zn serum in patients with pulmonary TB with DM and without DM. The research method used is descriptive-analytical with a cross-sectional approach. The results showed that the average level of iron (Fe) serum in patients with pulmonary TB was 111.67 μg / dL, and the average level of iron (Fe) serum in patients with pulmonary TB with DM was 61.23, μg / dL. For serum zinc levels, the average level of zinc (Zn) serum in patients with pulmonary TB was 101.29 μg / dL, and the average level of zinc serum in patients with pulmonary TB with DM was 76.38 μg / dL. The study concludes that there is a difference in the average levels of Fe and Zn in patients with pulmonary TB and patients with pulmonary TB with DM. Keywords: Fe, TB, TB-DM, Zinc